Structure Of Emotional And Defensive Patterns Among People with Different Levels Of Emotional Maturity - Piven, Мargarita (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article investigates features and manifestation of psychological defense mechanisms and stable emotional characteristics among test persons with different levels of emotional maturity. The dominant psychological defense mechanisms in both groups are considered. The differences in terms of psychological defense mechanisms in groups of people with high and low emotional maturity of personality are show. Four-factor structure of emotionally protective patterns in emotional maturity of personality is presented. The specifi manifestation of the emotionally protective structure depending on the severity of the studied phenomenon is found.